Analisis Penerapan Kode Etik Akuntan Dalam Menangani Kasus Pelanggaran Etika Profesi - F, Fita; Asan, Rima; Y, Yuliawati; Yasti, Ayu; Sinaga, Edro Rezeki (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the implementation of the accountant’s code of ethics in handling cases of professional ethical violations in Indonesia. Using a qualitative method through documentation studies, this research examines various real cases of ethical violations involving public accountants, such as the cases of KAP Petrus Mitra Winarta, KPMG Siddharta Siddharta Harsono, and PT Garuda Indonesia Tbk. The findings indicate that the accountant’s code of ethics plays a crucial role as a moral and professional guideline in maintaining integrity, objectivity, professional competence, confidentiality, and professional behavior. However, in practice, the implementation of the code of ethics still faces several challenges, including pressure from management, conflicts of interest, and weak supervision. Violations of the code of ethics can have serious consequences, affecting both the reputation of individuals and the profession as a whole, as well as reducing public trust in financial